A Quantitative Study of the Influence of Micro and Macro Influencers on Brand Awareness with Electronic Word of Mouth (eWOM) as a Mediation Variable on TikTok Users - Adhelia Qorimah Putri; Shandy Puspita (LPPM STMIK Mardira Indonesia, 2026)
This study seeks to investigate the mediating function of Electronic Word of Mouth (eWOM) in connecting the impact of Micro Influencers and Macro Influencers on Brand Awareness among TikTok users. In the evolution of digital marketing, Electronic Word of Mouth (eWOM) has emerged as a significant force influencing consumer perception and behavior, particularly through user interactions such as comments, reviews, and recommendations on social media. This study employs a quantitative methodology via a poll of 300 current TikTok users who have engaged with material from both Micro and Macro Influencers. Data were gathered via an online questionnaire and evaluated using linear regression and the Sobel Test for mediation in SPSS. The study's findings demonstrate that Micro Influencers and Macro Influencers exert a substantial impact on Electronic Word of Mouth (eWOM). Moreover, Electronic Word of Mouth (eWOM) has been shown to impact Brand Awareness significantly. The mediation test results demonstrate that Electronic Word of Mouth (eWOM) significantly mediates the relationship between influencers and Brand Awareness. The results indicate that influencers' efficacy in enhancing brand awareness relies not solely on audience reach but also on their capacity to foster interaction and communication among users through Electronic Word of Mouth (eWOM).